Nutritional rickets in twins: a case report - D. Frasca; G. Morganti; S. Cherubini (PAGEPress Publications, 2013)
Vitamin D deficiency rickets in infants attributable to inadeguate vitamin D intake and decreased exposure to sunligh continue to be reported in the United States and other Western Countries. The American Academy of Pediatrics raccomend that all infants, children and adolescent have a minumin intake of 400 UI of vitamin D per day. We describe a case of deficiency-related rickets in two moroccan twins aged 10 months.